The Role of Transformational Leadership on Firm Performance: Mediating Effect of Corporate Sustainability and Moderating Effect of Knowledge-Sharing - Shahzad, Muhammad Asim; Iqbal, Tahir; Jan, Naveed; Zahid, Muhammad (Frontiers in Psychology, 2022)
The primary purpose of the research is to investigate the mediating role of corporate sustainability in the relationship between the impacts of transformational leadership on performance of firms. This study study is also aimed to investigate the moderating role of knowledge sharing on the relationship of transformational leadership with corporate sustainability. Top management of small and medium size Chinese automobile sector were the responded of the study. The data was gathered by using self-administrative survey questionnaire and the data was analyzed using Smart PLS 3 software. The results of this study revealed that transformational leadership has positive and significant effect on performance of the firm. Corporate sustainability has significant meditating role in the association of transformational leadership and firm performance. Findings indicated that knowledge sharing has moderating role on the association of transformational leadership and firm performance. Findings of this study contribute to the body of knowledge and shows that leadership style has significant effect on the firm performance and knowledge sharing culture in firms are essential for better performance of the firm. Furthermore, firms may improve their performance by improving their sustainability and by creating knowledge sharing culture.